A Family’s fight in Racial Discrimination in Noughts + Crosses Novel by Malorie Blackman - Naufal, Muhammad Athallah (English Literature Study Program, 2023)
Racism has been a prevalent issue ever since the concept of race was known to mankind, due to this fact, a lot of kinds of racism emerged in society.This study explained the experiences of Callum and his family through the levels of racism as well as how they responded towards the racism itself in the novel Noughts + Crosses by Malorie Blackman. This study itself is a literary criticism focusing on sociological approaches by employing two theories, one by Camarra Phylis Jones named levels of racism (2000) and the second one is multimotive theory by Richman & Leary (2009). Based on the analysis of this study, the first level of Jones’ theory seems to be the most prominent out of the three which is the institutional racism, the characters in this novel were restricted or has limited access to quite a lot of government infrastructure, silenced voice, as well as small quantity of representative in power. While the personally-mediated racism manifested itself through the suspicion of minorities; especially Callum, lack of respect from the Crosses, devaluation of minorities’ capabilities, scapegoating, and dehumanization through hate crime and police brutality. In internalized racism there is also evidence of whiteness as in Lynette’s case where she believes herself to be black as well as self-devaluation by the characters themselves for example Ryan who used the slur word to his own race. Callum and his family responded with various types of response, such as Jude who is leaning towards being more aggressive after the experience of racism while Callum at least try to regain relational value within the society with relationship-promoting response as well as trying to exclude or withdraw himself from the society with avoidance or withdrawal response.